Diarylethenes Display In Vitro Anti-TB Activity and Are Efficient Hits Targeting the Mycobacterium tuberculosis HU Protein - María Angélica Suarez; Jhesua Valencia; Christian Camilo Cadena; Raktim Maiti; Chandreyee Datta; Gloria Puerto; José Hipólito Isaza; Homero San Juan; Valakunja Nagaraja; Juan David Guzman (Molecules, 2017)
Tuberculosis continues to be a great source of concern in global health because of the large reservoir of humans infected with the bacilli and the appearance of clinical isolates resistant to a wide array of anti-tuberculosis drugs. New drugs with novel mechanisms of action on new targets are urgently required to reduce global tuberculosis burden. Mycobacterium tuberculosis nucleoid associated protein (NAP) HU has been shown to be druggable and essential for the organism’s survival. In this study, four diarylethenes were synthesized using a one-pot decarboxylated Heck-coupling of coumaric acids with iodoanisoles. The prepared compounds 1–4 were tested for their in vitro growth inhibition of M. tuberculosis H37Rv using the spot culture growth inhibition assay, displaying minimum inhibitory concentrations between 9 and 22 µM. Their cytotoxicity against BHK-21 cell line showed half inhibition at concentrations between 98 and 729 µM. The most selective hit (SI = 81), demonstrated inhibition of M. tuberculosis HU protein involved in maintaining bacterial genome architecture.